Membentuk Karakter Anak dengan Gembala yang Baik: Perspektif Yehezkiel 34:1-6 - Miryam Sunbanu; Nirwana Sunbanu; Malik Bambangan (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
In the era of globalization, the world is increasingly developing rapidly, humans no longer pay attention to ethics, morals, and human character. The author sees the role of various parties as very necessary, namely from parents and especially from a shepherd who is entrusted by God in controlling children who have fallen into the current of the development of the era. So in this case, the role of a serious shepherd is very necessary to educate and shape the character of good children. This article offers how a shepherd can play a role in the formation of a child’s character. The author is aware that currently most children are experiencing a character crisis that is not controlled by the influence of the era of technological and scientific development. Therefore, the shepherd is expected to carry out his duties well, earnestly and in accordance with the teachings and learning of the Christian faith. The goal is to form and create a good generation, with noble morals, responsible and has a character like Christ.